KURANGNYA KECAPAKAN SISWA TERHADAP PENGGUNAAN MICROSOFT EXCEL: BAGAIMANA KORELASINYA DENGAN PENGOLAHAN DATA AKUNTANSI? - Assifa Fitriyah; Mega Renanda Putri; Septianesa Anggraeni; Siti Rahma Munawaroh; Yuliani Ismawati; Heni Mulyani; Rama Wijaya Abdul Rozak (Jurnal Pijar, 2023)
This article discusses the ability of accounting students in using Excel for accounting purposes. This is studied due to a discrepancy in understanding the correlation between these two variables. Therefore, as researchers, we want to delve into this issue to find the correct answer. The research was conducted using quantitative methods and correlation analysis to prove the correlation between Excel and accounting. The variables will be tested to determine if they have a correlation with each other. This will be done by giving a test through g-form, and the students will complete the test under the supervision of the teacher and the researcher. The enthusiasm of the students in completing the test is very high, and during the research, many students were eager to ask about the given test. The results of the study will be processed with Microsoft Excel using the Correl formula. It turns out that the two variables have a very weak correlation or are not related. This is evidenced by the assessment that students who have high scores in Excel are not followed by high scores in Excel for accounting. On the other hand, students who have high scores in Excel for accounting are not followed by high scores in Excel. Perhaps the reason for the low score in Excel for accounting is due to the incomplete level of Excel learning for the tested students, and the rarity of using Excel for accounting in vocational high school, as MYOB is usually the application that is frequently used.